A potent novel vaccine adjuvant based on straight polyacrylate - Marie Garinot; Fabienne Piras-Douce; Patricia Probeck; Véronique Chambon; Kucku Varghese; Yuanqing Liu; Ernesto Luna; Donald Drake; Jean Haensler (Elsevier, 2020)
A structure-activity study was conducted to identify the structural characteristics underlying the adjuvant activity of straight (i.e. non-crosslinked) polyacrylate polymers (PAAs) in order to select a new PAA adjuvant candidate for future clinical development. The study revealed that the adjuvant effect of PAA was mainly influenced by polymer size (Mw) and dose. Maximal effects were obtained with large PAAs above 350 kDa and doses above 100 μg in mice. Small PAAs below 10 kDa had virtually no adjuvant effect. HPSEC analysis revealed that PAA polydispersity index and ramification had less impact on adjuvanticity. Heat stability studies indicated that residual persulfate could be detrimental to PAA stability. Hence, this impurity was systematically eliminated by diafiltration along with small Mw PAAs and residual acrylic acid that could potentially affect product safety, potency and stability. The selected PAA, termed SPA09, displayed an adjuvant effect that was superior to that of a standard emulsion adjuvant when tested with CMV-gB in mice, even in the absence of binding to the antigen. The induced immune response was dominated by strong IFNγ, IgG2c and virus neutralizing titers. The activity of SPA09 was then confirmed on human cells via the innate immune module of the human MIMIC® system.